A comparative study of intra-cervical foley’s catheter and PGE2 gel for pre-induction cervical ripening - Alam, Anjuman; Ahmed, Eyaqub Ali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical ripening, before induction of labour, is needed to increase the success of labour induction, to reduce complications and to diminish the rate of cesarean section and duration of labour. Pharmacological preparations are in widespread use for cervical ripening but are not free from side-effects and complications. Mechanical methods, i.e. the use of Foley’s catheter balloon, though effective have not gained much popularity because of the fear of infection. Therefore, this study has been conducted to prove the efficacy and safety of extra amniotic Foley catheter balloon and to compare it with intra-cervical prostaglandin E2 (PGE2) gel. The objective of this study was to the success of induction of labor depends on the cervical status at the time of induction. For effective cervical ripening both Foley's catheter and PGE2 gel are used. The aim of this study was to compare the efficacy of intra cervical Foley's catheter and intra cervical PGE2 gel in cervical ripening for the successful induction of labor. Methods: A randomized, comparative study was conducted in the department of obstetrics and gynaecology, Assam Medical College and Hospita, Dibrugarh, during a period of one year from July 2014 to June 2015. 200 patients at term with a Bishop's score ≤3 with various indications for induction were randomly allocated to receive (100 pts) intra-cervical Foley's catheter or PGE2 gel (100 pts). After 6 hours post induction, Bishop's score was noted, labor was augmented if required. Statistical analysis was done using Chi square test and t test. Results: The groups were comparable with respect to maternal age, gestation age, indication of induction and initial Bishop's score. Both the groups showed significant change in the Bishop's score, 5.10±1.55 and 5.14±1.60 for Foley's catheter and PGE2 gel, respectively, P<0.001; However there was no significant difference between the two groups. There was no significant difference in the side effects and caesarean section rate in both groups. The induction to delivery interval was 16.01±5.50 h in group F and 16.85±3.81 h in group P (p = 0.073). Apgar scores, birth weights and NICU admissions showed no significant difference between the two groups. Conclusions: This study shows that both Foley's catheter and PGE2 gel are equally effective in pre induction cervical ripening.